The 5-HTTLPR polymorphism of the serotonin transporter gene and child's sex moderate the relationship between disaster-related prenatal maternal stress and autism spectrum disorder traits: The QF2011 Queensland flood study. (October 2019) - Laplante, David P.; Simcock, Gabrielle; Cao-Lei, Lei; Mouallem, Maya; Elgbeili, Guillaume; Brunet, Alain; Cobham, Vanessa; Kildea, Sue; King, Suzanne
Abstract: The 5-HTTLPR polymorphism of the serotonin transporter has been shown to play a role in autism spectrum disorders (ASD). Moreover, disaster-related prenatal maternal stress (PNMS) has also been shown to be associated with ASD. However, no study to date has examined whether these two factors, either individually or in combination, are predictive of ASD traits in the same sample. We hypothesized that children, particularly boys, with the LL genotype exposed to high levels of disaster-related PNMS would exhibit higher levels of ASD traits compared to boys with the LS or SS genotypes and girls regardless of genotype. Genotype and ASD levels obtained using the Australian normed Autism Spectrum Rating Scales – Short Form were available for 105 30-month-old children exposed to varying levels of PNMS following the 2011 Queensland Flood. For boys, higher ASD traits were associated with the 5-HTTLPR LL genotype in combination with either a negative maternal appraisal of the flood, or high levels of maternal composite subjective stress, PSTD-like or peritraumatic dissociation symptoms. For girls, maternal peritraumatic dissociation levels in combination with the 5-HTTLPR LS or SS genotype were associated with higher ASD traits. The present findings are the first to demonstrate that children's genotype moderates effects of disaster-related PNMS on ASD traits, with different pattern according to child sex.